VALIDITAS PERANGKAT PEMBELAJARAN BIOLOGI TERINTEGRASI KEARIFAN LOKAL UNTUK MENGEMBANGKAN KETERAMPILAN PENYELESAIAN MASALAH MAHASISWA - Septiana dwi Utami; Ika Nurani Dewi (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2017)
Abstract : Problem solving skills are skills that need to be developed in biology learning. Biology learning goals are not only to improve the understanding of the concept of living things, but also need to strive for a balance between science knowledge and the value of local wisdom. One way to train these skills is to apply learning that is integrated with local wisdom. Learning devices developed in this study need to be validated by experts. The validation result of the feasibility of the learning device from the component aspect of content, language, and presentation is included in the valid category.